MANAJEMEN SUPERVISI AKADEMIK PENGAWAS DI MTS NEGERI 2 OGAN ILIR - Rini Yusmarti; Yasir Arafat; Dessy Wardiah (Jurnal As-Salam, 2020)
Abstract: The focus of this research is on the supervisory management of academic supervisors at MTs Negeri 2 Ogan Ilir. The research objective is to look at how to manage academic supervision in MTs Negeri 2 Ogan Ilir, such as planning, implementing, evaluating, and following up on academic supervision. This research uses a qualitative approach. The results obtained from the perspective of academic supervision planning at MTs Negeri 2 Ogan Ilir can be said to work well with the supervision planning program. Academic oversight by supervisors at MTs Negeri 2 Ogan Illir has been carried out but not yet optimal because the frequency of visits is still lacking. An evaluation of academic oversight at MTs Negeri 2 Ogan Ilir has been carried out but not yet effective. The follow-up of the academic supervision conducted by the supervisor in MTs Negeri 2 Ogan Ilir is quite adequate. Keywords: Management, Academic Supervision, and Supervisor. Abstrak: Fokus penelitian ini pada manajemen pengawas akademik pengawas di MTs Negeri 2 Ogan Ilir. Tujuan penelitian adalah untuk melihat bagaimana mengelola pengawasan akademik di MTs Negeri 2 Ogan Ilir, seperti perencanaan, pelaksanaan, evaluasi, dan menindaklanjuti pengawasan akademik. Jenis penelitian menggunakan pendekatan kualitatif. Hasil penelitian diperoleh dari sisi perencanaan pengawasan akademik di MTs Negeri 2 Ogan Ilir dapat dikatakan berhasil dengan baik dengan program perencanaan pengawasan. Pengawasan akademik oleh pengawas di MTs Negeri 2 Ogan Illir telah dilakukan tetapi belum optimal karena frekuensi kunjungan masih kurang. Evaluasi pengawasan akademik di MTs Negeri 2 Ogan Ilir telah dilakukan tetapi belum efektif. Tindak lanjut dari pengawasan akademik yang dilakukan oleh pengawas di MTs Negeri 2 Ogan Ilir cukup memadai. Kata Kunci: Manajemen, Pengawasan Akademik, Pengawas.